76.0k views
0 votes
What is the solution of the system y equals 10 x -2 + y equals - x + 3

2 Answers

2 votes
y = 10x - 2
y = -7x + 3

10x - 2 = -7x + 3
10x + 7x = 3 + 2
17x = 5
x = 5/17

y = -7x + 3
y = -7(5/17) + 3
y = -35/17 + 3
y = -35/17 + 51/17
y = 16/17

solution is (5/17,16/17)
User James Wise
by
5.4k points
7 votes

y = 10x - 2

y = -x + 3

Set the two equations equal to each other (as both equal y)

10x - 2 = -x + 3

Solve for x. Isolate the x.

10x (+x) - 2 (+2) = -x (+x) + 3 (+2)

10x + x = 3 + 2

11x = 5

Isolate the x. Divide 11 from both sides

11x/11 = 5/11

x = 5/11

Plug in 5/11 to one of the equations

y = -x + 3

y = -(5/11) + 3

y = -5/11 + 33/11

y = 28/11

x = 5/11, y = 28/11

hope this helps

User MilesStanfield
by
5.6k points